Morphodynamics of Cold High Latitude Semiarid Regions: The Example of Ellef Ringnes Island, Nunavut - St-Onge, Denis; Gullentops, Frans (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn this paper we use the example of Ellef Ringnes Island, Nunavut, to examine active geomorphic processes in a high latitude semiarid region. The spectacular landscape of Ellef Ringnes Island is principally the result of fluvial erosion controlled by geological structure. The nival regime concentrates flow in a brief late-spring period which provides strong erosive capabilities for rivers in spite of low annual precipitation. Other processes related to the cold environment produce a variety of minor landforms such as patterned ground, mud flows associated with ground ice, and solifluction lobes.